VD_FINDINFO Jug / 2025 / 348 vom 17. Dezember 2024 - VD Tribunal cantonal (2024)
MAUVAIS TRAITEMENTEN GÉNÉRAL, HOMOSEXUALITÉ, LIBERTÉ SEXUELLE, EXPULSIONDROIT PÉNAL, TOXICOMANIE | 56 CP, 66a al. 1 let. c CP, 66a al. 2 CP